Immune-Related Adverse Events Are Associated With Clinical Benefit in Patients With Non-Small-Cell Lung Cancer Treated With Immunotherapy Plus Chemotherapy: A Retrospective Study - Morimoto, Kenji; Yamada, Tadaaki; Takumi, Chieko; Ogura, Yuri; Takeda, Takayuki; Onoi, Keisuke; Chihara, Yusuke; Taniguchi, Ryusuke; Yamada, Takahiro; Hiranuma, Osamu; Morimoto, Yoshie; Iwasaku, Masahiro; et al. (Frontiers in Oncology, 2021)
Background The immunotherapy plus chemotherapy combination is one of the most promising treatments in advanced non-small-cell lung cancer (NSCLC). Immunotherapy often causes immune-related adverse events (irAEs), which have been reported to be associated with the good clinical outcomes. However, the effects of immunotherapy plus chemotherapy remain unknown. In this study, we investigated the association between irAEs caused by immunotherapy plus chemotherapy and clinical efficacy in patients with advanced NSCLC. Materials and Methods We retrospectively analyzed the data of patients with advanced NSCLC, who received a combination of immunotherapy plus chemotherapy at six institutions in Japan between January 2019 and September 2019. We examined the effect of irAEs on various clinical outcomes. Results We included 70 patients with advanced NSCLC. Patients were divided into two groups: patients with irAEs and patients without irAEs. Patients with irAEs had significantly longer progression-free survival than those without irAEs on univariate (hazard ratio 0.53, 95% confidence interval 0.30–0.93, p = 0.026) and multivariate (hazard ratio 0.53, 95% confidence interval 0.29–0.97, p = 0.041) analyses. In addition, patients with grade 1–2 irAEs (mild irAEs) had significantly longer progression-free and overall survival than those with grade 3-5 irAEs (severe irAEs) or without irAEs on univariate (398 days versus 189 days, respectively; p = 0.0061) and multivariate (not reached versus 412 days, respectively; p = 0.021) analyses. Conclusion Patients with NSCLC who experienced mild irAEs showed better response to treatment with immunotherapy plus chemotherapy than those with severe irAEs or without irAEs. Further large-scale research is warranted to confirm these findings.